Early and Late Strength Characterization of Portland Cement Containing Calcined Low-Grade Kaolin Clay - Mark Bediako; S. K. Y. Gawu; A. A. Adjaottor; John Solomon Ankrah (Journal of Engineering)
Heat treated low-grade kaolin clays are now considered as a suitable pozzolanic material to metakaolins. However their suitability as a good pozzolanic material depends on the geochemistry and structure of the clay which is usually influenced by the geographical environment. This study investigated a low-grade kaolin clay from Nyamebekyere in the Ashanti Region of Ghana. The influence of the calcined material on the early and late strength development of Portland cement was analyzed. The early 3- and 7-day strength as well as the late 28-day strength of Portland cement replaced with 20% by weight of the calcined material yielded the optimum strength values. Further analysis using Solid State Magic Angle Spinning Nuclear Magnetic Resonance (Ss MAS NMR) probed into the Aluminium (Al) environment to detect the presence and nature of Al hydrates using the optimum mixture proportion. The Ss MAS NMR results showed that the strength enhancement of the optimum mixture was due to the growth of stable monosulphate compounds at the octahedral environment resulting from metastable aluminate phases at the tetrahedral environment. For greater reliability on concrete strength performance, the study recommends the use of 20% calcined clay of Nyamebekyere clay as Portland cement replacement.